Medicina ancestral montubia como atractivo del turismo de salud en la Provincia de los Ríos - Valencia Franco, Maria De Los Angeles (2021)
This research is carried out in order to recognize Montubia ancestral medicine as an attractiveness of health tourism in the province of Los Ríos, since it aims to analyze the incidence of ancestral medicine as an attractiveness of health tourism in the province of Los Ríos . It is important to have knowledge of traditional medicine in the province of Los Ríos, the places where it occurs, since traditional medicine has many benefits which contribute to health, prevent different diseases and even end the disease many times. The research techniques of this case study are based on: documented research and the survey was used as a technique to determine the ancestral Montubia medicine as an attractiveness for health tourism in the province of Los Ríos. In addition, a survey was conducted on the population of this province, which was chosen randomly. The tourist activity has a close relationship with ancestral medicine, because it is present in the different communities, thus creating a medicinal tourism that allows exchange with cultures, knowledge between tourists and the inhabitants of a community